The Oxford history of the British Empire. Vol. 3, The nineteenth century - Louis, William Roger, 1936-; Porter, Andrew; Low, Alaine M. (Oxford ; New York : Oxford University Press, 2009)
Volume III of The Oxford History of the British Empire covers the long nineteenth century, from the achievement of American independence in the 1780s to the eve of world war in 1914. This was the period of Britain's greatest expansion as both empire-builder and dominant world power. The volume is divided into two parts. The first contains thematic chapters, some focusing on Britain, others on areas at the imperial periphery, exploring those fundamental dynamics of Britishexpansion which made imperial influence and rule possible. They also examine the economic, cultural, and institutional frame.
Cover; Contents; List of Maps; List of Figures; List of Tables; Abbreviations and Location of Manuscript Sources; List of Contributors; 1. Introduction: Britain and the Empire in the Nineteenth Century; PART I; 2. Economics and Empire: The Metropolitan Context; 3. Economics and Empire: The Periphery and the Imperial Economy; 4. British Migration and the Peopling of the Empire; 5. Migration from Africa, Asia, and the South Pacific; 6. British Policy, Trade, and Informal Empire in the Mid-Nineteenth Century; 7. Britain and Latin America; 8. Britain and China, 1842-1914.
Originally published 1999.
Includes bibliographical references and index.
Keywords: Imperialism -- History -- 19th century; New Books January 2001.; Great Britain -- Colonies -- History -- 19th century; Electronic books